Фауна некоторых групп беспозвоночных пойменных островов Днепра и влияние на нее антропических и абиотических факторов - Надворный, В.Г. (Вестник зоологии, 1982)
Six island groups and nine characteristic habitats with specific animal and plant associations a r erecognized within the Dnieper basin reservoirs. Invertebrate complex formation ismonitored in each island group, with special reference to the role of human and abiotic factors in their life. The data on species diversity, population dynamics and occurrence of certain species are given for each habitat.